The Correlation Between Mastering Vocabulary and The Students' Ability in Speaking (International Journal of Cultural and Social Science, 2023)
There are four major skills in learning English, they are: listening, reading, speaking and writing. Speaking for many years has occupied a large position of time in teaching and learning activities in the school. Speaking is an activity used by someone to communicate with others. It takes place everywhere and has become part of our daily activities. The aims of this research were: To know the students' ability in mastering vocabulary, to know the students' ability in speaking and to know the significant correlation between mastering vocabulary and the students ' ability in speaking. The research was done at MTs Islamiyah Medan. The population of the research was 125 students while the sample was 56 students taken using random sampling. And the instrument of the research test in analyzing data, the writer used the product moment correlation formula. Hath of this research was accepted if rcounter was bigger than stable, Ho of this research was rejected if rcounter was lower than rtable. From the data that was analyzed, it showed that ro is 0.877 and r table with a significant standard of 5% is 0.262. The product moment correlation value was bigger than the “r” table (0.877 > 0.262). There is Ha of the research was accepted, but Ho was rejected. Thus, it can be concluded that there was a positive correlation between mastering vocabulary and the students' ability in speaking.